2005
DOI: 10.1073/pnas.0503853102
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endothelial nitric oxide synthase by small RNA

Abstract: Repeats (27-nt) in intron 4 have been shown to play a cis-acting role in endothelial nitric oxide synthase (eNOS) promoter activity. We hypothesize that the 27-nt repeats could be the source of small nuclear RNA specifically regulating eNOS expression. In this study, we used synthesized 27-nt RNA duplex and found that the eNOS gene transcriptional efficiency was reduced 63% (0.047 ؎ 0.009 vs. 0.126 ؎ 0.015, P < 0.01) by nuclear run-on assay. In endothelial cells transfected with the 27-nt small RNA duplex, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 33 publications
5
84
0
1
Order By: Relevance
“…To distinguish these two possibilities, the transcriptional activities of wildtype and targeted BCL2 alleles were examined with nuclear run-on transcription analysis using a modified protocol with biotin-16-uridine triphosphate (UTP) (Patrone et al, 2000;Tong et al, 2005;Zhang et al, 2005). Results of nuclear run-on assays showed that the transcriptional activity of the targeted allele was 10.3-fold lower than that of the wild-type allele, indicating the expression discrepancy of the wild-type and the targeted BCL2 alleles was mainly due to the difference in transcriptional activities between the two alleles (DCT ¼ 34.13-30.77E3.36; 2 3.36 ¼ 10.3) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To distinguish these two possibilities, the transcriptional activities of wildtype and targeted BCL2 alleles were examined with nuclear run-on transcription analysis using a modified protocol with biotin-16-uridine triphosphate (UTP) (Patrone et al, 2000;Tong et al, 2005;Zhang et al, 2005). Results of nuclear run-on assays showed that the transcriptional activity of the targeted allele was 10.3-fold lower than that of the wild-type allele, indicating the expression discrepancy of the wild-type and the targeted BCL2 alleles was mainly due to the difference in transcriptional activities between the two alleles (DCT ¼ 34.13-30.77E3.36; 2 3.36 ¼ 10.3) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear run-on assay The transcriptional activity of wild type and of targeted BCL2 alleles was determined by nuclear run-on transcription analysis according to a modified protocol that uses biotin-16-uridine triphosphate (UTP) (Roche, Sandhofer Strasse, Mannheim, Germany) (Patrone et al, 2000;Tong et al, 2005;Zhang et al, 2005). Briefly, 2-3 Â 10 7 Nalm6-1 cells were washed twice with ice-cold PBS and resuspended in cell lysis buffer containing 10 mM Tris-HCl (pH 7.4), 3 mM MgCl 2 , 10 mM NaCl, 150 mM sucrose and 0.5% NP-40.…”
Section: Construction Of the Bcl2 Targeting Vectormentioning
confidence: 99%
“…2B). Nuclear run-on experiments (18) in HEK-293 cells, performed at the 20-and 40-h time points after transfection of control or miR-320 duplexes, indicated that increased levels of mature miR-320 induced TGS of the POLR3D gene (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zhang et al have shown that the 27 bp repeats in eNOS intron 4 produce small 27 bp micro RNAs [37,38]. This intron-based micro RNA can induce gene specific transcriptional suppression by modifying histone acetylation and DNA methylation, which may serve as an effective negative feedback regulator of eNOS expression.…”
Section: Discussionmentioning
confidence: 99%